A dual-targeting triplebody mediates preferential redirected lysis of antigen double-positive over single-positive leukemic cells - Schubert, Ingo; Saul, Domenica; Nowecki, Stefanie; Mackensen, Andreas; Fey, Georg; Oduncu, Fuat S. (Mabs, 2014)
The single-chain triplebody HLA-ds16-hu19 consists of three single-chain Fv (scFv) antibody fragments connected in a single polypeptide chain. This protein with dual-targeting capacity mediated preferential lysis of antigen double-positive (dp) over single-positive (sp) leukemic cells by recruitment of natural killer (NK) cells as effectors. The two distal scFv modules were specific for the histocompatibility protein HLA-DR and the lymphoid antigen CD19, the central one for the Fc gamma receptor CD16. In antibody-dependent cellular cytotoxicity (ADCC) experiments with a mixture of leukemic target cells comprising both HLA-DR sp HuT-78 or Kasumi-1 cells and (HLA-DR plus CD19) dp SEM cells, the triplebody mediated preferential lysis of the dp cells even when the sp cells were present in <=20-fold numerical excess. The triplebody promoted equal lysis of SEM cells at 2.5-fold and 19.5-fold lower concentrations than the parental antibodies specific for HLA-DR and CD19, respectively. Finally, the triplebody also eliminated primary leukemic cells at lower concentrations than an equimolar mixture of bispecific single-chain Fv fragments (bsscFvs) separately addressing each target antigen (hu19-ds16 and HLA-ds16). The increased selectivity of targeting and the preferential lysis of dp over sp cells achieved by dual-targeting open attractive new perspectives for the use of dual-targeting agents in cancer therapy.
EVALuna2:1718